THEORETICAL ANALYSIS OF THE PROBLEM OF MOTHERHOOD AND PARENTAL INSTITUTIONS IN MODERN PSYCHOLOGY - Ignatenko О.В. (Pedagogy of Higher and Secondary Education, 2022)
In the article some going is briefly given near consideration of maternity. Maternity is examined as a functional sphere setting of which consists in providing adequate arrxietics about children. Implementation of parent functions depends on the proper necessities and force of setting. An author examines a psychological problem related to the emotional state of woman in connection with implementation of its parent role.